THE MEASUREMENT OF BETA-ASYMMETRIES AT UNISOR NOF USING EXTERNAL PLASTIC SCINTILLATOR DETECTORS - Mantica, P; Kern, B; Zimmerman, B; Walters, W; Rikovska, J; Stone, N (Kluwer Academic Publishers, 1992)
The performance of two external plastic scintillator detectors has been tested in an off-line mode using a source of106Ru Fe at UNISOR/NOF. The measurement of beta asymmetries at various temperatures has resulted in the reproduction of the previously-determined magnetic dipole moment for the 1+ ground state of106Rh and in addition the conclusion that the sign of this moment is positive. © 1992 J.C. Baltzer A.G., Scientific Publishing Company.